D-mannose-modified iron oxide nanoparticles for stem cell labeling - Horak, Daniel; Babic, Michal; Jendelová, Pavla; Herynek, Vít; Trchová, Miroslava; Pientka, Zbynek; Pollert, Emil; Hájek, Milan; Syková, Eva (Bioconjugate chemistry, 2007)
New surface-modified iron oxide nanoparticles were developed by precipitation of Fe(II) and Fe(III) salts with ammonium hydroxide according to two methods. In the first method, precipitation was done in the presence of D-mannose solution (in situ coating); the second method involved oxidation of precipitated magnetite with sodium hypochlorite followed by addition of D-mannose solution (postsynthesis coating). Selected nanoparticles were characterized by transmission electron microscopy (TEM), atomic force microscopy (AFM), elemental analysis, dynamic light scattering, infrared (IR), X-ray powder analysis, and ultrasonic spectrometry. While the first preparation method produced very fine nanoparticles ca. 2 nm in diameter, the second one yielded ca. 6 nm particles. Addition of D-mannose after synthesis did not affect the iron oxide particle size. UV-vis spectroscopy suggested that D-mannose suppresses the nonspecific sorption of serum proteins from DMEM culture medium on magnetic nanoparticles. Rat bone marrow stromal cells (rMSCs) were labeled with uncoated and d-mannose-modified iron oxide nanoparticles and with Endorem (Guerbet, France; control). Optical and transmission electron microscopy confirmed the presence of D-mannose-modified iron oxide nanoparticles inside the cells. D-mannose-modified nanoparticles crossed the cell membranes and were internalized well by the cells. Relaxivity measurements of labeled cells in gelatin revealed very high relaxivities only for postsynthesis D-mannose-coated iron oxide nanoparticles.
Keywords: železité sloučeniny; roztoky; buňky stromatu; Particle Size; Ferric Compounds; spektrální analýza; Spectrum Analysis; buňky kostní dřeně; Mannose; Stromal Cells; krysa rodu Rattus; kovové nanočástice; Stem Cells; Animals; Metal Nanoparticles; Solutions; Microscopy, Electron, Transmission; mannosa; zvířata; barvení a značení; velikost částic; Rats; Staining and Labeling; Bone Marrow Cells; kmenové buňky; transmisní elektronová mikroskopie